1988
DOI: 10.1111/j.1651-2227.1988.tb10737.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation with Levamisole in Children with Frequently Relapsing Steroid Responsive Nephrotic Syndrome

Abstract: ABSTRACT. The immunological and clinical effects of levamisole were studied in 10 children with frequently relapsing steroid responsive nephrotic syndrome (SRNS). The efficacy of the drug was tested during remission of the disease with all patients on alternate day steroid therapy. The lymphocyte proliferative response to phytohemagglutinin (PHA), concanavalin‐A (Con‐A) and pokeweed mitogen (PWM) were normal. The Con‐A induced suppressor T‐lymphocyte activity of 7 patients was low before treatment with levami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…The immunomodulatory agent levamisole has been used as an adjunctive therapy in such patients [31,32,33,34,35,36,37,38] as a good alternative to major immunosuppressives [39]. This treatment leads to decreases in the number of relapses and the amount of prednisolone required.…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory agent levamisole has been used as an adjunctive therapy in such patients [31,32,33,34,35,36,37,38] as a good alternative to major immunosuppressives [39]. This treatment leads to decreases in the number of relapses and the amount of prednisolone required.…”
Section: Discussionmentioning
confidence: 99%
“…It is a randomized controlled clinical trial, using Ievamisole as the sole drug in the treatment group, keeping in mind the following facts, viz (a) initial remission is easily induced with corticosteroids with minimal side-effects [15], (b) relapses occurring in the first 6 months after attaining remission very often herald multiple subsequent relapses [17], (c) relapses are directly related to depression of T-cell function [7], (d) Ievamisole is known to restore T-cell function [10], (e) the responses obtained in most studies with Ievamisole were directed at inducing remission and not at maintaining remission [9,11], and (0 most studies recruited only multiple relapsers [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first publication of Tanphaichitr et al [6], several studies have suggested that levamisole reduces the frequency of relapses and diminishes steroid doses in steroid-dependent patients [7,8,9,10,11,12,13,14,15,16,17,18,19]. The majority of studies found levamisole to be free from serious side effects on a long-term basis.…”
Section: Introductionmentioning
confidence: 95%